Self Leadership and the One Minute Manager : Increasing Effectiveness Through Situational Self Leadership - Blanchard, Kenneth H; Fowler, Susan, 1951-; Hawkins, Laurence (New York : W. Morrow, 2005)
A business parable follows the experiences of young advertising executive Steve, who, on the brink of losing his job, learns from a gifted magician three empowering techniques that enable him to take responsibility for his situation
Do you believe in magic? -- People are not mind readers -- Elephant thinking -- Cycles of power -- Diagnose yourself -- Getting what you need -- Running together -- No excuses -- One minute magic -- Appendix: The business card trick
Keywords: Leadership; Self-management (Psychology); Leadership and Management; Self Leadership